State ownership and SMEs’ performance in Vietnam - Tran, Quoc Trung; Nguyen, Thi Mai; Nguyen, Tran Sy; Dao, Thi Huong; Nguyen, Quang Tam (Journal of International Economics and Management, 2024)
The debate on the impact of state ownership on firm performance has drawn considerable interest from both scholars and professionals in the field of corporate finance. However, prior research has primarily focused on listed firms, whose characteristics differ from those of small- and medium-sized enterprises (SMEs). Hence, this paper investigates how state ownership influences SMEs’ performance. The sample includes 5,092 firm-years from over 2,000 SMEs with state ownership in Vietnam from 2013 to 2019. The model was estimated using three regression methods, including fixed effects, random effects, and pooled ordinary least squares. The results show that state ownership is positively associated with SMEs’ performance. This finding implies that state ownership creates competitive advantages for SMEs rather than reducing their performance. Therefore, policymakers should consider the advantages and disadvantages of privatizing state-owned SMEs or reducing state ownership in these enterprises. Moreover, investors should divert their capital to state-owned SMEs and increase their value.